Advances in chiral separations by nonaqueous capillary electrophoresis in pharmaceutical and biomedical analysis. Issue 7 (1st October 2013) - Ali, Imran; Sanagi, Mohd Marsin; Aboul‐Enein, Hassan Y.; Phillips, Terry M.
<x xml:space="preserve">Abstract</x> NACE is an alternative technique to aqueous CE in the chiral separations of partially soluble racemates. Besides, partially water‐soluble or insoluble chiral selectors may be exploited in the enantiomeric resolution in NACE. The high reproducibility due to low Joule heat generation and no change in BGE concentration may make NACE a routine analytical technique. These facts attracted scientists to use NACE for the chiral resolution. The present review describes the advances in the chiral separations by NACE and its application in pharmaceutical and biomedical analysis. The emphasis has been given to discuss the selection of the chiral selectors and organic solvents, applications of NACE, comparison between NACE and aqueous CE, and chiral recognition mechanism. Besides, efforts have also been made to predict the future perspectives of NACE.